Bank control and the number of bank relations of Japanese firms - Kazuo Ogawa; Elmer Sterken; Ichiro Tokutsu (Center for Economic Studies and ifo Institute (CESifo), 2005)
We explore the determinants of the number of long-term bank relations of listed Japanese firms using a unique data set covering the period 1982-1999. Japanese listed firms have about seven long-term bank loan relations on average, but show a large variation around the average. We analyze the determinants of the choice for the number of bank relations. We use data on loan and equity ownership to address the impact of the Japan-specific bank-firm relations and bank control on the number of loans decision. Having a relation with a topequity holding bank reduces the number of bank relations, while debt-rich and cash-poor firms have more bank relations.
Keywords: G32; G21; 330; firm-bank relations; single versus multiple borrowing; bank control; discrete choice models; Bank; Unternehmen; Lieferanten-Kunden-Beziehung; Eigentümerstruktur; Schätzung; Japan; Hausbank